PENGGUNAAN ENZIM RENNET DAN BAKTERI Lactobacillus plantarum YN 1.3 TERHADAP SIFAT SENSORIS KEJU - Hutagalung, Truly M.; Yelnetty, A.; Tamasoleng, M.; Ponto, J.H.W. (Universitas Sam Ratulangi, 2017)
THE UTILIZING OF RENNET ENZYMES and Lactobacillus plantarum YN 1.3 BACTERIA ON SENSORY CHARACTERISTICS OF CHEESE. This research aims to determine the utilizing of rennet enzymes and Lactobacillus plantarum YN 1.3 bacteria on sensory characteristics of cheese. This experiment usingÂ a completely randomized design (CRD) with treatments level of rennet enzymes 10%, 8%, 6%, 4%, 2% and Lactobacillus plantarum YN 1.3 bacteria on 0%, 2%, 4%, 6%, 8% levels, which is each treatment repeated as much as 40 of replications (panelists) with hedonic method used. The result showed that the utilizing of rennet enzyme and Lactobacillus plantarum YN 1.3 bacteria gives highly signifant different effects (P<0,01) on cheese color, aroma, texture andÂ flavor. Based on the results of data analysis and discussions, can be concluded that cheese with rennet enzyme 2% and Lactobacillus plantarum YN 1.3 bacteria 8%, is the best performs and most preferred to panelists.Key words: Cheese, Rennet Enzyme, Lactobacillus plantarum YN 1.3.